2011
DOI: 10.1161/hypertensionaha.110.168906
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the AMP-Activated Protein Kinase-α2 Accentuates Agonist-Induced Vascular Smooth Muscle Contraction and High Blood Pressure in Mice

Abstract: The aim of the present study was to determine the effects and molecular mechanisms by which AMP-activated protein kinase (AMPK) regulates smooth muscle contraction and blood pressure in mice. In cultured human vascular smooth muscle cells (HMSC), we observed that activation of AMPK by AICAR (5-aminoimidazole-4-carboxamide 1-beta-D-ribofuranoside) inhibited agonists-induced phosphorylation of myosin light chain (MLC) and myosin phosphatase targeting subunit 1 (MYPT1). Conversely, AMPK inhibition with pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 35 publications
6
74
2
Order By: Relevance
“…Unexpectedly, this seemed not to be because of an activation of MLCP as reported earlier 18,32 but was associated with an increase in G-actin, as well as thinning and rarefaction of VSM-actin filaments. Our data are consistent with the view that this AMPK effect involves cofilin activation.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Unexpectedly, this seemed not to be because of an activation of MLCP as reported earlier 18,32 but was associated with an increase in G-actin, as well as thinning and rarefaction of VSM-actin filaments. Our data are consistent with the view that this AMPK effect involves cofilin activation.…”
Section: Discussionsupporting
confidence: 60%
“…AMPK can induce smooth muscle relaxation directly by a decrease of [Ca 2+ ] i or of Ca 2+ sensitivity. [16][17][18][19][20][21] In a recent study, we identified AMPK as a new potential upstream kinase of the sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) regulator phospholamban and a regulator of the BK Ca (large conductance calcium-activated potassium) channel in microvascular smooth muscle. Nonetheless, there was still an additional, slowly developing vasodilation, which was probably Ca 2+ -independent because it was still observed after inhibition of SERCA BK Ca .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 Although ongoing studies in our laboratory indicate (slowly incipient) effects of AMPK on calcium sensitivity in resistance arteries as well, we focused in the present study on the mechanisms of calcium decrease. We identified 2 underlying mechanisms: increased SERCA activity as a result of enhanced phospholamban phosphorylation and, although to our surprise functionally less effective, smooth muscle hyperpolarization induced by stimulation of BK Ca channels.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although MLCK is generally accepted as a key regulator of smooth muscle contraction, 11 numerous studies during the past 3 decades have pointed to other systems for regulation of the degree of tension developed and borne by smooth muscle. Notably, the activity of myosin phosphatase is highly regulated by both calcium-dependent and calcium-independent mechanisms, [12][13][14][15] and numerous hypotheses champion thin filament-based regulation, 16 including alterations in cytoskeletal structures. 17 Smooth muscle actomyosin cross-bridges not only rapidly generate tension but also hold tension.…”
Section: Article See P 562mentioning
confidence: 99%